2018
DOI: 10.1016/j.jval.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methods for the Mapping of Utilities Using Mixture Models: Mapping the AQLQ-S to the EQ-5D-5L and the HUI3 in Patients with Asthma

Abstract: BackgroundStudies have shown that methods based on mixture models work well when mapping clinical to preference-based methods.ObjectivesTo develop these methods in different ways and to compare performance in a case study.MethodsData from 856 patients with asthma allowed mapping between the Asthma Quality of Life Questionnaire and both the five-level EuroQol five-dimensional questionnaire (EQ-5D-5L) and the health utilities index mark 3 (HUI3). Adjusted limited dependent variable mixture models and beta-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…The ndings provide evidence that different predictive models should be used for mapping EQ-5D-3L, EQ-5D-5L, HUI3 and SF-6D in our sample. Our analyses showed that both versions of the EQ-5D utility scores were best predicted by the beta mixture regression model which is consistently reported in other studies [14][15][16]. Our mapping algorithm for the HUI3…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ndings provide evidence that different predictive models should be used for mapping EQ-5D-3L, EQ-5D-5L, HUI3 and SF-6D in our sample. Our analyses showed that both versions of the EQ-5D utility scores were best predicted by the beta mixture regression model which is consistently reported in other studies [14][15][16]. Our mapping algorithm for the HUI3…”
Section: Discussionsupporting
confidence: 85%
“…The beta regression mixture model is a two-part model that incorporates a multinomial logit model and a beta mixture model in their algorithms. Studies have increasingly suggested that this regression method outperforms linear regression model [14][15][16].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…These regression methods can be extended to mapping to EQ-5D HSUVs from other country value sets as well as other measures e.g. Gray et al 2018 [212] uses these approaches for HUI3. The appropriateness of methods will depend on the measure and distribution as well as standard tests applied to assess these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some populations were mixed, for example, Chen, 2015 [62], Richardson, 2014 [63] used the Multi-instrument Comparison (MIC) dataset [253] which has all the generic PBMs and contains both patients (selfidentified) and members of the general population who were healthy. A number of studies relied on the MIC dataset to undertake mapping within specified patient populations including asthma [69,212], depression [64], diabetes [65,202], cancer [205] and heart disease [68].…”
Section: General Description Of Studiesmentioning
confidence: 99%
“…The probability of being in each component is estimated using a multinomial logit model. In this study, we used a beta-mixture model which has recently been introduced by Gray et al [15,16] based on the truncated inflated beta regression model [17]. This is a two-part model including a multinomial logit model and a beta-mixture model.…”
Section: Discussionmentioning
confidence: 99%